Large-scale school meal programs and student health: Evidence from rural China - Wang, Jingxi; Hernandez, Manuel A.; Deng, Guoying (International Food Policy Research Institute, 2021)
Reducing urban-rural gaps in child health and nutrition is one of the most difficult challenges faced by many countries. This paper evaluates the impact of the Nutrition Improvement Program (NIP), a large-scale school meal program in rural China, on the health and nutritional status of compulsory education students aged 6-16. We use data from multiple rounds of the China Health and Nutrition Survey between 2004-2015 and implement a quasi-experimental approach exploiting cross-county variations in program implementation. We find that NIP participation is, on average, associated with a higher height-for-age z-score in the order of 0.22-0.42 standard deviations. The impacts are larger among students in a better health condition but small or not significant among the most disadvantaged. We do not observe heterogeneous effects across several individual and household characteristics. We also do not find significant effects on Body Mass Index-for-age and weight-for-age z scores. The results suggest that NIP partially improved students’ health over the first years of implementation, but more support is needed to achieve broader impacts that effectively reach all vulnerable students. Several robustness checks support our findings.